PENGUKURAN ARAH KIBLAT TEMPAT IBADAH DENGAN APLIKASI ARAH KIBLAT DAN AZIMUT MATAHARI - Nailur Rahmi; Yoga Agustio (JURIS (Jurnal Ilmiah Syariah), 2021)
This study examines the comparison of the Qibla direction using the Qibla direction application with the Sun Azimuth method. The problem is that there are many methods that can be used in measuring the Qibla direction especially in today's technological era. One such method is the Android-based Muslim Pro application. From these problems the question arises, namely how to position the Qibla direction using the Qibla direction application and the Sun Azimuth method, then what are the advantages and disadvantages of the Sun Azimuth method with the Muslim Pro Qibla direction application in determining the Qibla direction. This research is a field research. Data obtained through Ephemeris data, interviews and measurements using both methods. After the data collected, it is processed by means of Persistent observation, Triangulation, using reference materials. Then the data is analyzed in a cooperative way, namely comparing the measurement results of the Muslim Pro Qibla direction application with the measurement results of the Sun Azimuth method. This study found that there are differences in measurement results between the Sun Azimuth methods in the application of the Muslim Pro Qibla direction.